A state-of-the-art review on Ag/AgCl ion-selective electrode used for non-destructive chloride detection in concrete. (1st November 2020) - Zhang, Zhangmin; Hu, Jie; Ma, Yuwei; Wang, Yangyang; Huang, Haoliang; Zhang, Zuhua; Wei, Jiangxiong; Yin, Suhong; Yu, Qijun
Abstract: The accurate measurement of chloride content in concrete is of great importance, because chloride-initiated corrosion of the reinforcement significantly influences the durability of reinforced concrete. This paper summarizes the research status of Ag/AgCl ion-selective electrode (ISE) used for non-destructive chloride detection in concrete. In general, four main topics are reviewed, including preparation of Ag/AgCl-ISE, main factors influencing the potential of Ag/AgCl-ISE, detection limit/potential response of Ag/AgCl-ISE, and novel composites/electrochemical methods based on Ag/AgCl-ISE for chloride detection in concrete. Further, the existing problems and research strategies are also discussed in detail in this present review.